Contraceptive Use and Sexual Behavior in Obese Women - Kaneshiro, Bliss (Seminars in Reproductive Medicine, 2012)
Obesity and unintended pregnancy differentially affect women based on sociodemographic factors. Because of the overlap of these factors, obesity and unintended pregnancy have been described as colliding epidemics. Understanding the relationship between obesity and unintended pregnancy, contraceptive use, and sexual behavior is important in improving the reproductive health of women given the increasing weight demographic. A review of the literature reveals contraceptive use versus nonuse does not differ in women of different body weights. Obese women use oral contraceptives less than normal weight women and are more likely to use procedural methods like sterilization. No difference was noted in most types of sexual behavior for women of different body weights.
Keywords: contraceptive; obese; sexual behavior; unintended pregnancy; birth control